Adequação da metodologia do teste de envelhecimento acelerado em sementes de rúcula - Alves, Charline Zaratin; de Sa, Marco Eustaquio [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The use of high vigor seed constitutes basic and fundamental. Given the increasing development os the seeds industry and the improvement of vigor tests used to differentiate subtle variations in the quality of seeds of vegetable crops, is needed. The objective was to study variations in conducting the accelerated aging test, to verify their sensitivity for identifying different vigor levels of arugula seed. Were used the cultivars Cultivada and Gigante, using five lots of seeds for each. The seeds were subjected to the determination of water content, germination, first germination, emergence of seedlings and variations in the accelerated aging test, without salt solution ( traditional procedure) and with salt solution in 48, 72 and 96 hours; at 38 degrees C, 41 degrees C and 45 degrees C. The accelerated aging test in traditional procedure is not efficient to evaluation the vigor of arugula seeds. The accelerated aging test with saline solution using the combination 41 degrees C for 72 hours, was sensitive to evaluated of the physiological potential of arugula seeds.
Methodology adequation for accelerated aging test in arugula seeds
Keywords: Eruca sativa; vegetable; quality physiology; vigor